2005
DOI: 10.1007/s10350-005-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil and Idiopathic Anal Ulceration

Abstract: Failure to recognize nicorandil as an etiologic factor in the development of anal ulceration, when other potential underlying well-recognized inflammatory or neoplastic processes have been excluded, may lead to unnecessary surgical intervention in a group of high-risk patients. One of our patients had a potentially avoidable abdominoperineal resection. Pharmaceutical manipulation with alternative antiangina medication may induce healing. Pharmacologic manipulation should be coordinated with a physician to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…The vascular steal phenomenon has been cited as a possible explanation [108,146], however, animal studies demonstrate an anti-ulcer activity of nicorandil [91,92] and the presence of oral ulceration renders a hypothesis of ischemia in the well-vascularized oral cavity doubtful [10]. A direct local toxic action induced by electrolyte disturbance has been considered, secondary to nicorandil's activity on ATPsensitive potassium channels [150][151][152]; a hypersensitivity involving non-keratinizing squamous epithelium lining specific areas of the oral cavity and lower anal canal has been suggested [18]: this however would not explain the ulcerating and fistulating disease involving other segments of the gastrointestinal tract. Patel et al [153] argued that nicorandil, in a dose-dependent manner, dephosphorylates myosin and so hinders the actin filament contraction that is necessary for cell migration, as would be required to repair mucosal microtrauma and surgical wounds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The vascular steal phenomenon has been cited as a possible explanation [108,146], however, animal studies demonstrate an anti-ulcer activity of nicorandil [91,92] and the presence of oral ulceration renders a hypothesis of ischemia in the well-vascularized oral cavity doubtful [10]. A direct local toxic action induced by electrolyte disturbance has been considered, secondary to nicorandil's activity on ATPsensitive potassium channels [150][151][152]; a hypersensitivity involving non-keratinizing squamous epithelium lining specific areas of the oral cavity and lower anal canal has been suggested [18]: this however would not explain the ulcerating and fistulating disease involving other segments of the gastrointestinal tract. Patel et al [153] argued that nicorandil, in a dose-dependent manner, dephosphorylates myosin and so hinders the actin filament contraction that is necessary for cell migration, as would be required to repair mucosal microtrauma and surgical wounds.…”
Section: Discussionmentioning
confidence: 99%
“…within the MHRA database. While no anal ulceration was formally mentioned in the IONA, it has been suggested that the overall incidence might be around 0.07% [18]. A higher rate was estimated by Colvin et al (0.37%) [19] in their retrospective cohort study, where the number of exposed was calculated from prescriptions in general practices.…”
Section: Nos "Intestinal Ulcerations" (13%)mentioning
confidence: 97%
See 3 more Smart Citations